Widths of balls and free boundary minimal submanifolds - Zhu Jonathan J. (Advanced Nonlinear Studies, 2023)
We observe that the kk-dimensional width of an nn-ball in a space form is given by the area of an equatorial kk-ball. We also discuss the relationship between widths and lower bounds for the area of a free boundary minimal submanifold in a space form ball.